Analysis of The Influence of The Family Support System on Adolescent Behavior - Putri, Lili Dasa; Stianda, Vero (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
This identity. There are at least three ways in which the family support system affects teenagers, first is financial, second is moral support, third is social control. If the social role of the family is home phenomena. This is in line with Emile Durkheim's idea of social facts, where a research is research that discusses how the family support system influences behavior in adolescents. Adolescents are the age group where individuals experience the transition from children to adultsnot carried out well, it will have a bad impact on teenagers, this can be seen from the broken. This age group tends to be unstable and emotional because they are at the stage of searching for their person's actions are based on the social facts that occur, namely anomic, egoistic and altruisticKeywords: Suppot Sistem, Keluarga, Perilaku Remaja